Lineage- and stage-specific activity of antigen receptor gene enhancers during lymphocyte development - Ma, Fei; Braikia, Fatima Zohra; Sen, Ranjan (Frontiers in Epigenetics and Epigenomics, 2024)
Lymphocyte development culminates with generation of mature B and T cells that express unique antigen receptors on the cell surface. Genes that encode the two chains of B or T cell receptors are generated via DNA recombination and expressed sequentially during development, guided by locus activating enhancer sequences. In this review we summarize our understanding of molecular mechanisms that activate these enhancers in a lineage and developmental stage-specific manner. We draw attention to 1) the distinction between chromatin accessibility and transcriptional activation of these loci, 2) incomplete understanding of mechanisms that regulate B versus T cell-specific enhancer activity and 3) transcription factors that contribute to stage-specific enhancer activation within each lineage.